In Vitro Antibacterial Activity Test of Ethanolic Extract of Kersen (Muntingia calabura L.) Leaves Against the Growth of Escherichia coli - Abigail Eugelia Veterine Angsar; Rr Listyawati Nurina; Gottfrieda Patiencia Taeng-Ob Adang; Arley Sadra Telussa (Cendana Medical Journal, 2025)
Background: Diarrhea is a global health problem that causes millions of deaths every year. Treating diarrhea often involves the use of antibiotics, but antibiotic resistance is a serious problem. Cherry plants (Muntingia calabura L.) has been used traditionally to treatt infections . This research can provide new insights regarding the potential of using cherry plants as an alternative for treating bacterial infections without relying only on antibiotics. Objective: To determine the antibacterial activity of ethanol extracts from the cherry leaves (Muntingia calabura L.) against the Escherichia coli growth. Methods: This research is using a true experimental method with a post-test only control group design. The bacteria used is Escherichia coli with 8 treatment groups, the positive control group using ciprofloxacin, the negative control group using sterile aquadest, and six concentrations of cherry leaf extract treatment groups. The data was analyse with One Way Anova test. Results and Discussion: Inhibition zones produced at the concentrations of 100%, 50%, 25%, 12.5%, 6.25%, 3.125% measuring 15.39 mm ; 14.02 mm; 11.82 mm; 10.82 mm; 9.64 mm; 8.32 mm , indicating strong to moderate antibacterial effects. Conclusion: Ethanol extracts of cherry leaves (Muntingia calabura L.) exhibit antibacterial activity against Escherichia coli in vitro. Keywords: Ethanol Extracts from Cherry Leaves, Antibacterial Activity, Escherichia coli, in vitro.